The matrilineal society of Meghalaya: trends of family planning and its implications on maternal health - Shullai, Wansalan Karu; Singh, A. Santa; Agarwal, Manika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The key health indicators pertaining to maternal health are TFR, contraceptive usage and MMR. As per the NFHS V, the use of any contraceptive method is 27.4% and total fertility rate is 2.9 in Meghalaya, which reflects on the poor performance of the state towards achieving the goals set by the National Health Policy 2017. The current MMR of Meghalaya is 211/1 lakh live birth, one of the highest amongst the Indian states. The two most important causes of maternal mortality in Meghalaya are post-partum haemorrhage and anaemia- both avoidable causes of maternal mortality related to higher order pregnancies and lack of adequate spacing between two consecutive pregnancies, thereby increasing the importance of contraceptive use. The aim of the study was to identify factors associated with poor uptake of contraceptive measures and their implications on maternal health in a matrilineal society. Methods: A cross sectional study was conducted in the department of obstetrics and gynaecology, NEIGRIHMS where 200 patients, indigenous to Meghalaya, were recruited over a period of one year and were interviewed using a validated questionnaire pertaining to family planning practices. Results: Factors such as number of live births, religion and residence were seen to influence the utilization of contraceptive methods. Conclusions: There is still a wide gap to be filled- more sincere and dedicated efforts are needed to empower women to make informed decisions by increasing awareness about the importance of family planning and its implications on maternal health.